Perancangan Usulan untuk Mereduksi Waste Produk TWD-DHT-K002 dengan Value Stream Mapping pada CV. Sinar Baja Electric - Ryo Reynardo; Nova Sepadyati (Jurnal Titra, 2022)
In a manufacturing company, a production process is one thing that is very concerned. In a production process, there are activities that are classified as activities that do not add value to the product. This is called a non-value added activity. Therefore, analysis and improvement can help to reduce waste contained in the production process of making TWD-DHT-K002 products. The method used to analyze the existence of non-value added activities is value stream mapping. This method can help to map the actual production flow and can help classify activities that are value added and non-value added. The result of this research is a time comparison of value added, non-value added from before and after the proposal. The results obtained can be seen from the difference in Manufacturing Cycle Efficiency (MCE). MCE before the proposal was 0.40% while after the proposal was 0.41%. Then for the results of the comparison of the percentage before and after the proposed value added and non-value added on the TWD line, the value added increased by 7.82%. Non-value added decreased by 6.63% while for necessary non-value added decreased by 1.19%. While on line A3 for value added it increases by 1.52% and necessary non-value added decreases by 1.52%.